Modest Residual Effects of Short-Term Warming, Altered Hydration, and Biocrust Successional State on Dryland Soil Heterotrophic Carbon and Nitrogen Cycling - Tucker, Colin; Ferrenberg, Scott; Reed, Sasha C. (Frontiers in Ecology and Evolution, 2020)
Biological soil crusts (biocrusts) on the Colorado Plateau may fuel carbon (C) and nitrogen (N) cycling by soil heterotrophic organisms throughout the region. Late successional moss and lichen biocrusts in particular can increase soil C and N availability, but some data suggest these biocrust types will be replaced by early successional cyanobacterial biocrusts as the region undergoes rapid warming. In this study, we evaluated the short-term interactive effects of biocrust successional state and elevated temperature on soil heterotrophic C and N cycling (specifically, respiration, N2O emissions, microbial biomass C and N, and soluble C and N), using a two-phase approach consisting of an 87-day greenhouse mesocosm phase followed by a short-term (2-day) laboratory incubation phase. We found that biocrust successional state, as well as exposure to warmer temperatures during the mesocosm phase, had subsequent significant effects on the amount and temperature sensitivity of soil heterotrophic C and N cycling in laboratory incubations. Late successional biocrusts increased C and N cycling relative to early successional crusts, while warming reduced both the magnitude and the temperature sensitivity of C and N cycling. The inhibiting effect of warming was most evident in soils from beneath late successional biocrusts, suggesting that an overall effect of climate warming may be a marked shift in the soil C and N cycles in the region.